Assessment of mental workload, work ability and musculoskeletal disorders of firefighters - Mahnaz Mahnaz; Rohollah fallah; fereydoon Laal; Najaf Noorizade; Ebrahim Rahimi (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Firefighting is one of the occupations that require high physical and aerobic power due to the nature of the job and the physical demands of this profession. Therefore, the present study aimed to investigate the relationship among Work ability index (WAI), mental workload, musculoskeletal disorders (MSDs) and their effective factors in firefighters. Methods:  This study was a cross-sectional study, which was carried out on 250 firefighters in Tehran. Data were collected using WAI, NASA-TLX and Body Discomfort Chart (BDC). Data analysis was carried out using descriptive statistics, linear regression, Pearson correlation and Spearman tests. Results: The mean and standard deviation of the total WAI score was 38.85±1.17. Also, the highest amount of mental workload was devoted to the physical load dimension (93.49±8.93). Meanwhile, the total mental load was also 70.07 ± 6.58. The results showed that the WAI is increased by 0.14 by augmentation of one unit at the academic level of firefighters (P = 0.03). The most common discomfort was reported in the lower (20%) and upper (16.8%) regions of the back. The total WAI relationship with total mental workload was positive and insignificant (P>0.05). There was a significant and reverse association between WAI and discomfort in wrist, leg and ankle. Conclusion: Despite the low rate of MSDs, even mild symptoms of musculoskeletal pain should be considered. Given the high level of mental workload, improving physical, psychosocial and social working conditions is important in increasing the ability of employees and augmenting the ability of their occupational activity.